Risk Factors Related to Stunting - Oktaviani, Tri Anugrah; Suwarni, Linda; Selviana, Selviana (Research and Community Service Unit, Poltekkes Kemenkes Kupang, 2023)
Childhood stunting, or low height for age, continues to be a concern for world health since it raises the possibility of both mortality and growth and development disorders. West Kalimantan province ranks seventh with the highest prevalence of 29.8% by 2021. But little is known about Pontianak's children's stunting risk factors, especially in the UPT Puskesmas Pal Lima (one of the community health centers with a high prevalence of stunting). The study aimed to determine risk factors associated with stunting in the UPT Puskesmas Pal Lima, such as high-risk pregnant women, pregnant women with chronic energy deficiency, communication of educational information about stunting, occupancy density, and age of pregnant women in the UPT Puskesmas Pal Lima. Cross-sectional study design was used. The research was conducted in February-March 2023. The population in this study were all stunted toddlers in the UPT work area of the Pal Lima Health Center. Sampling used quota sampling with all 75 stunted toddlers. Data analysis used univariate and bivariate analysis (chi square test with 95% CI). This research found that 61,3% with high risk pregnant women, 21,3% with chronic energy deficiency, 52% not exposed to information communication and education about stunting, 32% occupancy density were not qualified, 48% risk at age of pregnant mothers, 32% severe stunting and 68% stunting. There was a significant relationship between high-risk pregnant women (p-value = 0,015), pregnant women with chronic energy deficiency (p-value = 0,001), the information communication and education about stunting (p-value = 0,046), occupancy density (p-value = 0,043), and the age of pregnant women (p-value = 0,049), and the incidence of stunting in toddlers in the working area of UPT Puskesmas Pal Lima, West Pontianak District. Based on the results of this study can be used as a basis for the primary prevention of stunting in pregnant women.